Identifikasi Bakteri Escherichia Coli pada Ikan Kakap Merah (Lutjanus Malabaricus) di Laboratorium Badan Pengendalian dan Pengawasan Mutu Hasil Kelautan dan Perikanan (BPPMHKP) Makassar - Jemri, Jemri; Basran, Basran; Samsidar, Samsidar; Nasarudin, Abdul Rohman; Yuventi, Adelina (Syntax Literate, 2025)
Fish is a highly nutritious food source that is widely consumed by the public. One type of fish that has economic value and is often consumed is red snapper (Lutjanus malabaricus). However, the high water content in fish makes it easily contaminated by Escherichia coli bacteria, which can reduce quality and endanger consumer health. The final project aims to identify the presence of E. coli in red snapper (Lutjanus malabaricus) which was tested at the Laboratory of the Quality Control and Supervision of Marine and Fisheries Products (BPPMHKP) Makassar. The test was carried out based on the Indonesian National Standard (SNI 01-2332.1-2015) on microbiological methods, which includes the stages of sample preparation, presumptive test, confirmation test, observation of colony morphology, and biochemical tests. The media used include Butterfield's Phosphate Buffered (BFP), Lauryl Tryptone Broth (LTB), EC Broth, Levine's Eosin Methylene Blue (LEMB) Agar, and Plate Count Agar (PCA). The test results showed that the red snapper sample tested positive for Escherichia coli, indicated by a color change to metallic green on LEMB agar. Based on these results, it can be concluded that the tested red snapper was contaminated with Escherichia coli, thus failing to meet microbiological food safety standards. These test results are expected to serve as a reference in monitoring the quality of marine fishery products to ensure their safety for public consumption.